Assessment of Ecotourism from the Perspective of the Sustainable Development Based on SWOT Model (Case: Azerbaijan Region of Iran) - Hosseinalizadeh, Saghar; Jabbari, Sevda; Haghlesan, Masoud (European Journal of Sustainable Development, 2018)
The most important industry in sustainable tourism is ecotourism that contains a deep relationship with the sustainable development. Additionally, majority of countries focus on this connection. In this paper, reviewing theoretical foundations of the sustainable development and ecotourism, using experts’ opinions and analyzing the current status of Azerbaijan, Iran has been addressed according to tourist areas in the form of SWOT Table and by assessing all ecotourism and sustainable development indices a relationship between these concepts has been discussed. The conceptual model of the paper is based on "analytical-descriptive" method that has been examined by collecting information and theoretical data from scientific, documented bases, literature study and the research observations. The results indicate a shortage of water resources, ecological changes, environmental pollution, institutions’ ignorance, lack of urban services and infrastructure, illegal hunting and low cultural level of people in maintaining and finally increasing rural to urban migration and environmental degradation. Keywords: Ecotourism; Sustainability; Azerbaijan Iran; SWOT model